2008
DOI: 10.1002/chin.200828096
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Asymmetric Ring Opening of meso‐Epoxides with Aromatic Amines Catalyzed by a New Proline‐Based N,N′‐Dioxide‐Indium Tris(triflate) Complex.

Abstract: Tris(triflate) Complex. -Optically pure amino alcohols are obtained by the title reaction from stilbene oxide or its p-tolyl and 2-naphthyl analogues using N,N'-dioxide (Ia) as ligand. Cyclohexene oxide gives the corresponding amino alcohols with high yields and good enantioselectivities under similar conditions using dioxide (Ib) as ligand. -(GAO, B.; WEN, Y.; YANG, Z.; HUANG, X.; LIU, X.; FENG*, X.; Adv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In recent years, chiral amino alcohols have found a distinct role as chiral ligands for various metal-catalyzed asymmetric organic transformations. [1][2][3][4][5][6][7][8] To synthesize chiral b-amino alcohols, several strategies, namely, aminohydroxylation of olefins, 9,10 addition of a-hydroxy ketones to imines, [11][12][13] aminolytic kinetic resolution of racemic terminal/trans aromatic epoxides, [14][15][16][17][18] and asymmetric ring opening (ARO) of meso-epoxides, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have been reported in the literature. Among these, metal-catalyzed ARO of meso-epoxides with amines is one of the most elegant, atom efficient, and straightforward strategies for the synthesis of chiral b-amino alcohols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, chiral amino alcohols have found a distinct role as chiral ligands for various metal-catalyzed asymmetric organic transformations. [1][2][3][4][5][6][7][8] To synthesize chiral b-amino alcohols, several strategies, namely, aminohydroxylation of olefins, 9,10 addition of a-hydroxy ketones to imines, [11][12][13] aminolytic kinetic resolution of racemic terminal/trans aromatic epoxides, [14][15][16][17][18] and asymmetric ring opening (ARO) of meso-epoxides, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have been reported in the literature. Among these, metal-catalyzed ARO of meso-epoxides with amines is one of the most elegant, atom efficient, and straightforward strategies for the synthesis of chiral b-amino alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, metal-catalyzed ARO of meso-epoxides with amines is one of the most elegant, atom efficient, and straightforward strategies for the synthesis of chiral b-amino alcohols. Various chiral metal complexes of titanium, [19][20][21] vanadium, 22 niobium, 23,24 copper, 25 lanthanides, 4,6,8,26,27 chromium, 14,15 scandium, 7,28,29 indium, 30,31 and bismuth 32,33 have been used to catalyze this reaction effectively. Recently, Zhou et al 34 also reported the use of chiral Ti(IV) salen complex for ARO of meso epoxides with dithiophosphorous acid as nucleophile, but catalyst recycling was not attempted.…”
Section: Introductionmentioning
confidence: 99%